Lake storage variation on the endorheic Tibetan Plateau and its attribution to climate change since the new millennium - Yao, Fangfang; Wang, Jida; Yang, Kehan; Wang, Chao; Walter, Blake A.; Crétaux, Jean-François (My University, 2018)
Alpine lakes in the interior of Tibet, the endorheic Changtang Plateau (CP), serve as ‘sentinels’ of regional climate change. Recent studies indicated that accelerated climate change has driven a widespread area expansion in lakes across the CP, but comprehensive and accurate quantiﬁcations of their storage changes are hitherto rare. This study integrated optical imagery and digital elevation models to uncover the ﬁne spatial details of lake water storage (LWS) changes across the CP at an annual timescale after the new millennium (from 2002–2015). Validated by hypsometric information based on long-term altimetry measurements, our estimated LWS variations outperform some existing studies with reduced estimation biases and improved spatiotemporal coverages. The net LWS increased at an average rate of 7.34 ± 0.62 Gt yr−1 (cumulatively 95.42 ± 8.06 Gt), manifested as a dramatic monotonic increase of 9.05 ± 0.65 Gt yr−1 before 2012, a deceleration and pause in 2013–2014, and then an intriguing decline after 2014. Observations from the Gravity Recovery and Climate Experiment satellites reveal that the LWS pattern is in remarkable agreement with that of regional mass changes: a net effect of precipitation minus evapotranspiration (P-ET) in endorheic basins. Despite some regional variations, P-ET explains ∼70% of the net LWS gain from 2002–2012 and the entire LWS loss after 2013. These ﬁndings clearly suggest that the water budget from net precipitation (i.e. P-ET) dominates those of glacier melt and permafrost degradation, and thus acts as the primary contributor to recent lake area/volume variations in endorheic Tibet. The produced lake areas and volume change dataset is freely available through PANAGEA (https://doi.pangaea.de/ 10.1594/PANGAEA.888706).
Citation: Yao, F., Wang, J., Yang, K., Wang, C., Walter, B. A., & Crétaux, J.-F. (2018). Lake storage variation on the endorheic Tibetan Plateau and its attribution to climate change since the new millennium. Environmental Research Letters, 13(6), 064011. https://doi.org/10.1088/1748-9326/aab5d3
Keywords: Alpine lakes; Changtang Plateau; Endorheic Tibet; Lake water storage; Climate change; Satellite altimetry